Common Pepper Cultivars for Florida Production - Gene McAvoy (EDIS, 2008)
IPM-204, a 2-page illustrated fact sheet by G. McAvoy, is part of the Grower’s IPM Guide for Florida Tomato and Pepper Production. It lists pepper varieties currently popular with Florida growers. Published by the UF Department of Entomology and Nematology, December 2007.